Ecology and gut content analysis of mudskippers in selected mangrove areas - Masyitah, Mohd Ibrahim (Universiti Malaysia Sarawak (UNIMAS), 2012)
A study on ecology and gut content analysis of mudskippers was conducted in mangrove areas of Telaga Air and Muara Tebas, Kuching. A total of 31 individuals of mudskippers were collected using cast net and manually collected by hands. The morphometric and meristic characteristics were observed and recorded. The body total length (TL), standard length (SL), body weight (BW), and number of fins were measured. Identification was done using key features from Murdy (1989). Thirty one specimens were dissected to collect their gut content and to determine the frequency of occurrence (%). A total of 6 food items were found and classified as organic matter detritus (fine and coarse particulate organic matter), plant fragments, sand grains, crustacean (shrimp and crab), Nematode (worm), diatoms and microalgae. The most dominant food items in gut content of B. boddarti were diatoms and microalgae (100 %), sand grains (80 %) and organic matter (70 %). The gut content analysis of B. pectinirostris indicate that the most importance food items was diatoms and microalgae (100 %), plant fragments (66.7 %) and organic matter (55.6 %). In P. schlosseri, major food items were crustacean (100 %), sand grains (100 %), organic matter (66.7 %) and plant fragments (33.3 %).